Does family medicine training in Thailand affect patient satisfaction with primary care doctors? - Darin Jaturapatporn (2018)
Background. Recent national healthcare reforms in Thailand aim to transfer primary care to family physicians, away from more expensive specialists. As Family Medicine has yet to be established as a separate discipline in Thailand, newly trained family physicians work alongside untrained general doctors in primary care. While it has been shown that Family Medicine training programs in Thailand can increase the quality of referrals from primary care doctors to specialists, information is lacking about whether such training affects the quality of patient care. In the Department of Family Medicine at Ramathibodi Hospital, trained family physicians work with residents and general doctors. Although this situation is not typical within Thailand, it offers us the opportunity to look for variations in the levels of satisfaction reported by patients treated by different types of primary care doctor. Methods. During a two-week period in December 2005, 2,600 questionnaires (GPAQ) were given to patients visiting the Department of Family Medicine at Ramathibodi Hospital. Patients were given the choice of whether or not they wanted to participate in the study. A cross-sectional analysis was performed on the completed questionnaires. Mean GPAQ scores were calculated for each dimension and scored out of 100. Student t-tests, ANOVA with F-test statistic and multiple comparisons by Scheffe were used to compare the perceived characteristics of the different groups of doctors. Five dimensions were measured ranging from access to care, continuity of care, communication skills, enablement (the patient's knowledge of a self-care plan after the consultation) and overall satisfaction. Results. The response rate was 70%. There were significant differences in mean GPAQ scores among faculty family physicians, residents and general doctors. For continuity of care, patients gave higher scores for faculty family physicians (67.87) compared to residents (64.57) and general doctors (62.51). For communication skills, patients gave the highest GPAQ scores to faculty family physicians (69.77) and family medicine residents (69.79). For enablement, faculty family physicians received the highest score (82.44) followed by family medicine residents (80.75) and general doctors (76.29). Conclusion. Faculty family physicians scored higher for continuity of care when compared with general doctors and residents. General doctors had lower GPAQ scores for communication skills and enablement when compared to faculty family physicians and residents. Faculty family physicians had the highest GPAQ scores in many dimensions of family practice skills, followed by residents and general doctors. © 2007 Jaturapatporn and Dellow; licensee BioMed Central Ltd.